Plk1 and CK2 act in concert to regulate Rad51 during DNA double strand break repair. - Yata, K; Lloyd, J; Maslen, S; Bleuyard, J; Skehel, M; Smerdon, S; Esashi, F (2012)
Homologous recombination (HR) plays an important role in the maintenance of genome integrity. HR repairs broken DNA during S and G2 phases of the cell cycle but its regulatory mechanisms remain elusive. Here, we report that Polo-like kinase 1 (Plk1), which is vital for cell proliferation and is frequently upregulated in cancer cells, phosphorylates the essential Rad51 recombinase at serine 14 (S14) during the cell cycle and in response to DNA damage. Strikingly, S14 phosphorylation licenses subsequent Rad51 phosphorylation at threonine 13 (T13) by casein kinase 2 (CK2), which in turn triggers direct binding to the Nijmegen breakage syndrome gene product, Nbs1. This mechanism facilitates Rad51 recruitment to damage sites, thus enhancing cellular resistance to genotoxic stresses. Our results uncover a role of Plk1 in linking DNA damage recognition with HR repair and suggest a molecular mechanism for cancer development associated with elevated activity of Plk1.